(untitled) (CIPEEX, 2025)
INTRODUCTION: Cymbopogon martini may represent a promising species in the treatment of depression. In studies on depression therapy, natural-origin treatments have aroused increasing interest due to the adverse effects associated with conventional drugs and the long-standing traditional use of medicinal plants, although such therapies are not completely devoid of side effects. Geraniol is the main active constituent of Cymbopogon martini, popularly known as palmarosa, a grass from the Poaceae family, widely used in folk medicine and aromatherapy for its antimicrobial, anti-inflammatory, and relaxing properties. The essential oil extracted from this plant is rich in geraniol and monoterpenes, compounds that have been associated with antidepressant and central nervous system–modulating effects in studies conducted with Cymbopogon citratus and Cymbopogon winterianus. Reported adverse effects include sedative effects in mice and lethal effects in bees. However, no studies were found regarding the antidepressant potential of Cymbopogon martini. METHODOLOGY: This study will evaluate the antidepressant-like activity of extracts and/or essential oil of Cymbopogon martini in the forced swimming test in mice. The oil will be administered orally. The animals will undergo the forced swimming test for 6 minutes, with behavioral analysis performed during the last 4 minutes. Variables such as water temperature, sex, age, diet, dosage, overall health status, lighting, and environmental noise will be controlled. EXPECTED RESULTS: A reduction in immobility time following essential oil administration is anticipated, indicating an antidepressant-like effect. Additionally, no significant structural alterations in the liver and kidneys are expected, nor any clinical signs or symptoms suggesting organ impairment. CONCLUSION: This study proposes the scientific and experimental assessment of the antidepressant potential of Cymbopogon martini, a topic on which no previous research has been identified. The findings aim to contribute to the development of new therapeutic strategies with fewer side effects. The investigation seeks to explore antidepressant effects, possible adverse events, and elucidate the mechanisms of action.